Involvement of Ca2+ in Vacuole Degradation Caused by a Rapid Temperature Decrease in Saintpaulia Palisade Cells: A Case of Gene Expression Analysis in a Specialized Small Tissue. (4th May 2015) - Ohnishi, Miwa; Kadohama, Noriaki; Suzuki, Yoshihiro; Kajiyama, Tomoharu; Shichijo, Chizuko; Ishizaki, Kimitsune; Fukaki, Hidehiro; Iida, Hidetoshi; Kambara, Hideki; Mimura, Tetsuro
Abstract : Saintpaulia (African violet) leaves are known to be damaged by a rapid temperature decrease when cold water is applied to the leaf surface; the injury is ascribed to the chloroplast damage caused by the cytosolic pH decrease following the degradation of the vacuolar membrane in the palisade cells. In this report, we present evidence for the involvement of Ca 2+ in facilitating the collapse of the vacuolar membrane and in turn in the temperature sensitivity of Saintpaulia leaves. In the presence of a Ca 2+ chelator (EGTA) or certain Ca 2+ channel inhibitors (Gd 3+ or La 3+ ) but not others (verapamil or nifedipine), the pH of the vacuole, monitored through BCECF (2′, 7′-bis(carboxyethyl)-4 or 5-carboxyfluorescein) fluorescence, did not increase in response to a rapid temperature drop. These pharmacological observations are consistent with the involvement of mechanosensitive Ca 2+ channels in the collapse of the vacuolar membrane. The high level of expression of an MCA- (Arabidopsis mechanosensitive Ca 2+ channel) like gene, a likely candidate for a mechanosensitive Ca 2+ channel(s) in plant cells, was confirmed in the palisade tissue in Saintpaulia leaves by using a newly developed method of gene expression analysis for the specialized small tissues.